Study on Vibroacoustic Analysis of Marine Engine Supplied with Mixture of Fuels - Wróbel, Radoslaw; Andrych – Zalewska, Monika; Tkaczyk, Marcin (Recent Trends in Chemical and Material Sciences Vol. 2, 2021)
Researchers at the top crude oil companies are working at various eligible options like biodiesel, hydrogen, alcohols, compressed natural gas (CNG), liquefied petroleum gas (LPG). The main purpose of this article is to obtain differences in engine (Doosan MDT196TI) vibrations which was powered using two different fuel mixtures – liquefied natural gas with diesel pilot and diesel only. LNG and diesel oil differ in combustion temperature, density, and cetane numer; the combustion process of various fuels proceeds differently, so it has an impact on the generated vibroacoustic vibrations (vibrations have a direct impact on the degree of machine degradation). In research, diagnostic system is based on pizoelectric accelerometers and Digital Signal Processing operations (windowing, Fast Fourier Transform). In conclusions were used to analyze the results obtained, indicating how the tested fuels have an effect on vibrations